Tinjauan Potensi Olahraga Rekreasi Trekking Di Objek Wisata Air Terjun - Muhamat Ridwan; Anton Komaini; Alimuddin Alimuddin; Yogi Andria (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
This research started from the curiosity of researchers about the potential of trekking recreational sports at the Langkuik Tinggi Waterfalls of Malalak, Malalak District, Agam Regency. This study aims to see if there is a potential for recreational trekking at the Langkuik Tinggi Waterfalls of Malalak, Malalak District, Agam Regency. This research is a qualitative research, this research is intended to tell a situation or event that is actually there so that it just reveals facts and provides an objective explanation. Informants in this study were the Wali Nagari Malalak Selatan, the manager of the langkuik Tinggi Malalak waterfall, tourists/visitors, the surrounding community, and members of APGI (Indonesian Mountain Guides Association) who are also members of the Nature Lovers Basic Training Education team as experienced/ expert. Methods of data collection in this study through interviews, direct observation, and documentation. The results of this study reveal that: The Langkuik Tinggi Waterfalls of Malalak, Malalak District, Agam Regency has the potential to develop trekking recreational sports. This can be seen from the shape of the forest, rocky roads and rivers which are very suitable for trekking sports facilities.